THE INFLUENCE OF ROAD NETWORK DEVELOPMENT ON LAND USE (CASE STUDY: KARAWANG REGENCY, INDONESIA) - Irnanda Satya Soerjatmodjo (International Journal of Civil Engineering and Infrastructure, 2022)
The aims of this research are to find out the most influencing sector that brings huge impact towards the economic growth of Karawang regency after Jakarta-Cikampek toll road is established, and to generate the mathematical model which enables to serve information about the GDRP (Gross Domestic Regional Product) value of agriculture sector based on the impact of industrial sector GDRP value, trading sector DGRP value, and number of populations in Karawang regency.